Theoretical Study of Anti-Alzheimer’s Disease Using Molecular Modeling Methods - Ferdaous Hasni; Ismail Daoud; Nadjib Melkemi; Rania Kherachi (Proceedings)
Neurodegenerative diseases damage the nervous system and lead to a variety of complex progressive chronic issues [...]